2016
DOI: 10.1590/0103-6440201600152
|View full text |Cite
|
Sign up to set email alerts
|

Red LED Photobiomodulates the Metabolic Activity of Odontoblast-Like Cells

Abstract: Phototherapy has been indicated as an adjunctive treatment for tissue repair, including the pulp tissue. However, there are no defined irradiation parameters, which is a great challenge to the clinical use of phototherapy. The aim of this study was to evaluate the effect of phototherapy with red LED on odontoblast-like MDPC-23 cells, using different parameter settings. Cells were seeded (10 4 cells/cm²), incubated for 12 h in complete DMEM and then the culture medium was replaced by DMEM supplemented with 0.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the adjustable potentiometers of the broad range array allowed calibration to standardize the irradiance to achieve a baseline irradiance value of 3.5 mW/cm 2 at each wavelength (Figure ). This value was chosen since our previous study reported the stimulation of DPCs using red light emitting diodes (653 nm) at similar irradiance although other irradiances have also been shown to be effective for DPC stimulation. Furthermore, a lower irradiance is likely to be more clinically relevant since attenuation by dental tissues will reduce the irradiance delivered to dental pulp cells .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the adjustable potentiometers of the broad range array allowed calibration to standardize the irradiance to achieve a baseline irradiance value of 3.5 mW/cm 2 at each wavelength (Figure ). This value was chosen since our previous study reported the stimulation of DPCs using red light emitting diodes (653 nm) at similar irradiance although other irradiances have also been shown to be effective for DPC stimulation. Furthermore, a lower irradiance is likely to be more clinically relevant since attenuation by dental tissues will reduce the irradiance delivered to dental pulp cells .…”
Section: Resultsmentioning
confidence: 99%
“…Within a dental context, favourable data exists for oral health related conditions including oral mucositis [10], dentine hypersensitivity candidiasis and others . Odontoblast‐like cell modulation has also been reported which has significance for treatment of diseases such as dental caries . Stimulation of the dentine‐pulp complex has been shown to modulate oxidative stress and promote natural repair processes through reactive oxygen species (ROS) activation of latent transforming growth factors (TGF‐β1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The irradiation of cultured pulp cells was performed using a LED table; this device is widely employed in laboratorial studies in this research field (Fig. 1) [2,22,23,[39][40][41]. The LED table was developed by the Optical Group (OG) of the Optics and Photonics Research Center (Centro de Pesquisa em Óptica e Fotônica -CePOF) of the São Carlos Institute of Physics (IFSC) at the University of São Paulo (USP).…”
Section: Irradiation Devicementioning
confidence: 99%
“…The potential beneficial parameters (4 J/cm 2 , 15 J/cm 2 , and 30 J/cm 2 at 0.04 W/cm 2 ) [20,23,30,39,40], as well as more intense parameters, which may be considered to be potentially harmful to the cells (4 J/cm 2 , 15 J/cm 2 , and 30 J/cm 2 at 0.08 W/cm 2 ), were assessed. The irradiation parameters used in this study are shown in Tables 2 and 3.…”
Section: Irradiation Devicementioning
confidence: 99%